Handbook of open, distance and digital education - Zawacki-Richter, Olaf [Herausgeber]; Jung, Insung [Herausgeber] (Springer, 2023)
"This handbook offers a one-stop-shop for both new and established researchers, educators, policy makers and administrators in the field of open, distance and digital education (ODDE) to gain a comprehensive overview of the history, theory and practice at all levels of ODDE, and at the same time stimulates in-depth discussions on various themes and issues of ODDE for today and future. Researchers, scholars and students in the field of ODDE can use this handbook as a major reference to conduct their own research and learning agendas. To cover the field comprehensively, the handbook is structured following the 3M framework developed by one of the chief editors Zawacki-Richter. The 3M framework categorizes the major research areas and issues in ODDE on three levels. Accordingly, the handbook is divided into six sections in total, two section at each of the three levels: 1) Macro Level - ODDE Systems and Theories, 2) Meso Level - Institutional Perspectives, Management and Organization, and 3) Micro Level - Learning and Teaching in ODDE." (Publisher, BIBB-Doku)
Keywords: L 2.1 Lernformen; G 2.2.1 Technologisierung; L 4.2.3 Internetbasiertes Lernen / E-Learning; L 4.2.2 Klassisches Fernlernen; 370; Offenes Lernen; Fernunterricht; Computerunterstützter Unterricht; Digitalisierung; E-Learning; Open Educational Resources